Intermediary Metabolite Precursor Dimethyl-2-Ketoglutarate Stabilizes Hypoxia-Inducible Factor-1α by Inhibiting Prolyl-4-Hydroxylase PHD2 - Hou, Peifeng; Kuo, Ching-Ying; Cheng, Chun-Ting; Liou, Jing-Ping; Ann, David K.; Chen, Qiang (PLOS ONE, 2014)
Hypoxia-inducible factor 1α (HIF-1α), a major mediator of tumor physiology, is activated during tumor progression, and its abundance is correlated with therapeutic resistance in a broad range of solid tumors. The accumulation of HIF-1α is mainly caused by hypoxia or through the mutated succinate dehydrogenase A (SDHA) or fumarate hydratase (FH) expression to inhibit its degradation. However, its activation under normoxic conditions, termed pseudohypoxia, in cells without mutated SDHA or FH is not well documented. Here, we show that dimethyl-2-ketoglutarate (DKG), a cell membrane-permeable precursor of a key metabolic intermediate, α-ketoglutarate (α-KG), known for its ability to rescue glutamine deficiency, transiently stabilized HIF-1α by inhibiting activity of the HIF prolyl hydroxylase domain-containing protein, PHD2. Consequently, prolonged DKG-treatment under normoxia elevated HIF-1α abundance and up-regulated the expression of its downstream target genes, thereby inducing a pseudohypoxic condition. This HIF-1α stabilization phenotype is similar to that from treatment of cells with desferrioxamine (DFO), an iron chelator, or dimethyloxalyglycine (DMOG), an established PHD inhibitor, but was not recapitulated with other α-KG analogues, such as Octyl-2KG, MPTOM001 and MPTOM002. Our study is the first example of an α-KG precursor to increase HIF-1α abundance and activity. We propose that DKG acts as a potent HIF-1α activator, highlighting the potential use of DKG to investigate the contribution of PHD2-HIF-1α pathway to tumor biology.